2021
DOI: 10.2478/hjbpa-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

Decentralization in Tanzania: Perceptible Efficiency and Effectiveness in Management of Community Health Care, Free Basic Education and Public Private Partnership

Abstract: Decentralization has been a means to enhance efficiency and effectiveness in the management of local government affairs. Tanzania has undergone a reform through decentralization by devolution (D by D) and shifted relative power to lower levels of government known as local government authorities. The purpose is to improve the management of local government affair including the management of community health, free basic education and the management of contracts through public-private partnership. The objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Another model that was designed in line with Decentralisation by Devolution framework is Stigler's menu (1957) cited in Ebel & Yilmaz (1999) and Mkoma & Rwekaza (2021). This theory maintains that, the closer the government is to the people, the better it works and it also maintains that people should have the right to vote for the kind and amount of public services they want.…”
Section: Theorymentioning
confidence: 99%
“…Another model that was designed in line with Decentralisation by Devolution framework is Stigler's menu (1957) cited in Ebel & Yilmaz (1999) and Mkoma & Rwekaza (2021). This theory maintains that, the closer the government is to the people, the better it works and it also maintains that people should have the right to vote for the kind and amount of public services they want.…”
Section: Theorymentioning
confidence: 99%
“…The institution must have a management and administration system, a material basis and financial resources necessary for a stable shortand medium-term functioning, as well as human resources it can rely on, to achieve the proposed assumed objectives. The school principal is responsible for all these issues (Mkoma & Rwekaza, 2021). Educational effectiveness consists in mobilizing human and financial resources to get students to achieve the best possible results in learning (Tudoran Niculiţă et al, 2020).…”
Section: Specific Priorities In the Process Of Implementing A Qualitative Management Systemmentioning
confidence: 99%
“…Quality-focused educational management systematically values the community perspective, the school perspective, which proposes an education, defined as an authentic social exercise. In this context, based on continuity and change, the preoccupation to analyse the characteristics of the qualitative management becomes legitimate (Mkoma & Rwekaza, 2021). The qualitative management is an option related to educational policy.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is limited literature in Tanzania on the teachers' perception of the implementation of free basic education. Studies such as Doriye et al (2020); Hakielimu (2017); Khamis (2017); Mashala (2019); Shukia (2020); Kapinga (2017); Mbawala (2017); Awinia (2019); Shukran (2019); Tieng'o (2019); Mkoma and Rwekaza (2021); Mmasa (2020) focused on free education, but they have neglected the perception of teachers and concentrated on the issues of challenges, impact, community perceptions, management, the impact of stakeholder participation, gender disparities, general implementation, facilities, and resources. These studies have not shown how teachers perceive the policy they implement.…”
Section: Introductionmentioning
confidence: 99%